Analysis of Immediate versus Delayed Sternal Reconstruction with Pectoralis Major Advancement Versus Turnover Muscle Flaps - Kamel, George N.; Jacobson, Joshua; Rizzo, Amanda M.; Kinkhabwala, Corin; Lalezar, Frank; Draper, Lawrence; Tepper, Oren M.; Garfein, Evan S.; Weichman, Katie E. (Journal of Reconstructive Microsurgery, 2019)
Background The pectoralis major muscle flap is a versatile reconstructive option for deep sternal wound infections (DSWI). The timing and surgical technique of bilateral pectoralis major muscle advancement flaps versus unilateral pectoralis major muscle turnover and unilateral pectoralis major muscle advancement flap on patient outcomes remain to be elucidated. The purpose of this investigation was to compare timing, immediate versus delayed reconstruction, and the surgical technique in patients with deep sternal wounds infections on patient outcomes.Methods A retrospective review of patients who underwent sternal reconstruction with pectoralis major muscle was conducted. Patients diagnosed with DSWI after undergoing cardiac surgery were included for analysis. Patients were divided by flap timing and flap type for analyses. Bivariate tests were performed to compare patient clinical characteristics. Outcomes of interest were rates of postoperative complications, same admission mortality, reoperation, readmission, operating room time, and length of stay.Results A total of 88 patients were included for analyses (n = 57 bilateral advancement, n = 31 unilateral advancement with unilateral turnover; n = 62 immediate, and n = 26 delayed). Baseline characteristics did not differ between groups of flap type or timing. When postoperative complication rates were compared, the rate of tissue necrosis was significantly greater in patients with unilateral advancement with unilateral turnover flaps (n = 6 [19.4%]) compared with bilateral advancement flaps (n = 2 [3.5%]; p = 0.021). Mortality during admission did not differ with respect to flap type but differed significantly with respect to flap timing (immediate n = 7 [11.3%], delayed n = 9 [34.6%]; p = 0.015). Length of stay differed significantly by both type and timing (type: bilateral advancement = 26.9 ± 22.6 days, unilateral turnover = 38.0 ± 26.7 days, p = 0.042; timing: immediate = 26.8 ± 22.1 days, delayed = 40.2 ± 27.8, p = 0.019).Conclusion Patients who underwent pectoralis major muscle advancement flaps had lower incidence of tissue necrosis. Furthermore, the timing of immediate sternal reconstruction was associated with a decreased hospital length of stay.
Keywords: sternal reconstruction; turnover pectoralis major muscle flap; immediate versus delayed